Does acceptance of power distance influence propensities for problematic Internet use? Evidence from a cross‐cultural study. (17th December 2015) - Montag, Christian; Duke, Éilish; Sha, Peng; Zhou, Min; Sindermann, Cornelia; Li, Mei
Abstract: Introduction: Several studies suggest that Asian countries are particularly afflicted by problematic Internet use (PIU). Methods: The present study investigates whether individual differences in the acceptance of power distance can be linked to overuse of the Internet in Germany and in China. Power distance has been discussed as an essential dimension on which Asian and Western societies differ. In the present study, we investigate two large non‐clinical samples from Germany (n = 297) and China (n = 556) to address this question. Results: Both in Germany and in China, high acceptance of power distance was positively associated with PIU. These effects were more pronounced in China compared with Germany. Moreover, the observed effects were stronger in males compared with females. Discussion: Clearly, these findings are just a starting point and need to be replicated in the future. Clinical populations and a further important difference variable – collectivism – also merit consideration in future work.